2014
DOI: 10.1186/2008-2231-22-14
|View full text |Cite
|
Sign up to set email alerts
|

Genome expression analysis by suppression subtractive hybridization identified overexpression of Humanin, a target gene in gastric cancer chemoresistance

Abstract: Background: In cancer cells, apoptosis is an important mechanism that influences the outcome of chemotherapy and the development of chemoresistance. To find the genes involved in chemoresistance and the development of gastric cancer, we used the suppression subtractive hybridization method to identify the genes that are overexpressed in gastric cancer tissues compared to normal gastric tissues. Results: In the suppression subtractive hybridization library we constructed, the most highly overexpressed genes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 30 publications
(34 reference statements)
2
29
0
2
Order By: Relevance
“…In the context of cancer, the role of HN is poorly understood. HN is overexpressed in biopsies from patients with gastric 23 and bladder cancer 24 when compared to non-neoplastic surrounding tissue. We have previously shown that HN is overexpressed in rat pituitary tumor cells, when compared to normal pituitary cells 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of cancer, the role of HN is poorly understood. HN is overexpressed in biopsies from patients with gastric 23 and bladder cancer 24 when compared to non-neoplastic surrounding tissue. We have previously shown that HN is overexpressed in rat pituitary tumor cells, when compared to normal pituitary cells 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Although HN has been proposed to be a potential oncopeptide almost 2 decades ago 22 , its role in cancer development and treatment remains poorly understood. Since HN overexpression was detected in gastric cancer 23 , bladder tumor cells 24 , and pituitary tumor cells 13,18 , it was suggested that HN upregulation could play a role in tumorigenesis.…”
mentioning
confidence: 99%
“…189 Moreover, evidence has shown that humanin contributes to chemoresistance and cancer aggressiveness. 192,193…”
Section: Mitochondrion-derived Molecules Are Involved In Mitochondriamentioning
confidence: 99%
“…Su expresión fue detectada en cáncer gástrico, por lo que fue propuesto que la sobreexpresión de este péptido podría constituir un evento molecular impor-tante de la tumorigénesis y la quimiorresistencia del tumor (54). Más recientemente, también se informó su sobreexpresión en células tumorales de vejiga, por lo que se sugirió a la HN circulante en sangre como un potencial biomarcador para el diagnóstico de este tipo de cáncer (55).…”
Section: Hn Y Cáncerunclassified